Equation-of-state studies using laser-driven shock wave propagation through layered foil targets - Pant, H. C.; Shukla, M.; Senecha, V. K.; Bandyopadhyay, S.; Rai, V. N.; Khare, P.; Bhat, R. K.; Godwal, B. K.; Gupta, N. K. (Current science (Bangalore), 2002)
Results of laser-driven shock wave experiments for equation-of-state (EOS) studies of gold metal are presented. A Nd : YAG laser chain (2 Joule, 1.06 μm wavelength, 200 ps pulse FWHM) is used for generating shocks in the planar Al foils and Al + Au layered targets. EOS of gold in the pressure range of 9– 13 Mbar is obtained using impedance-matching technique. Numerical simulations performed using one-dimensional radiation hydrodynamic code supports the experimental results. Experimental data show remarkable agreement with results from studies using the existing standard EOS models and with other experimental data obtained independently using laser-driven shock experiments.